Mind the Gap! A transatlantic, intergenerational theatre project. Issue 2 (2nd July 2020) - Foster, Gill
ABSTRACT: This practitioner reflection explores the impact of a long-term inter-generational theatre project operating at the intersection between community and professional theatre practices in south-east London. The work developed through a creative partnership established between London South Bank University School of Performance, Southwark Playhouse and the New York Theatre Workshop whose intergenerational programme, Mind the Gap began in 2009. In this critically reflective essay, I seek to interrogate the precise nature of the impact of Mind the Gap! UK, derived from working with professional artists and processes within a community context. Writing in the journal of Health Promotion Practice, Anderson et al. observe that developing theatre performances from participants' own experience and stories creates a "unique space that release(s) participants from usual ways of thinking and interacting" and this has certainly proved to be true for the Mind the Gap ! ensembles. In order to understand how and what impact is generated, I will evaluate the key artistic and theatre practices which underpin the work and consider the precise nature of the effect of taking part in the project for both youth and elder participants.